2022
DOI: 10.1371/journal.pone.0271028
|View full text |Cite
|
Sign up to set email alerts
|

Semi-experimental assessment of neutron equivalent dose and secondary cancer risk for off-field organs in glioma patients undergoing 18-MV radiotherapy

Abstract: Neutron contamination as a source of out-of-field dose in radiotherapy is still of concern. High-energy treatment photons have the potential to overcome the binding energy of neutrons inside the nuclei. Fast neutrons emitting from the accelerator head can directly reach the patient’s bed. Considering that modern radiotherapy techniques can increase patient survival, concerns about unwanted doses and the lifetime risk of fatal cancer remain strong or even more prominent, especially in young adult patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Emerging studies have demonstrated that radiotherapy may substantially increase the risk of developing SPM in multiple cancers, such as breast cancer [ 13 ], nasopharyngeal carcinoma [ 14 ] and prostate cancer [ 15 ]. And some studies have investigated the optimal doses and theoretical strategies to reduce the risk of SPM for patients receiving radiotherapy [ 16 18 ]. The annual incidence of developing second primary lung cancer (SPLC) was 1.10% per patient, with an exceptionally high risk among young women with lung cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have demonstrated that radiotherapy may substantially increase the risk of developing SPM in multiple cancers, such as breast cancer [ 13 ], nasopharyngeal carcinoma [ 14 ] and prostate cancer [ 15 ]. And some studies have investigated the optimal doses and theoretical strategies to reduce the risk of SPM for patients receiving radiotherapy [ 16 18 ]. The annual incidence of developing second primary lung cancer (SPLC) was 1.10% per patient, with an exceptionally high risk among young women with lung cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the threshold energy for (γ, n) reaction is at least 8 MeV [6], neutron contamination in radiation therapy is of concerns in treatment with high-energy photons (> 10 MV). Recently, many researchers in the field of radiation protection have addressed the role and consequences of unwanted doses to the patient caused by photoneutrons [7][8][9]. Some efforts focused on reducing neutron production in the linac head through optimization of the Bremsstrahlung target [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the unwanted dose to the breasts of a patient undergoing 18 MV pelvic radiotherapy originates from photoneutrons by 67% [12]. Additionally, it has been shown that for glioma and hepatocellular patients undergoing 18 MV radiotherapy, secondary fatal cancer risk due to neutron contamination can reach 281 and 844 persons per one million persons, respectively [7,9]. For prostate patients undergoing 18 MV radiotherapy, it was reported that the total risk of secondary cancer in eye lenses, thyroid, and chiasma is 870 persons per one million persons [8].…”
Section: Introductionmentioning
confidence: 99%